1969
DOI: 10.1115/1.3591621
|View full text |Cite
|
Sign up to set email alerts
|

What Sound Can Be Expected From a Worn Tool?

Abstract: This paper describes an electronic-mechanical system which utilizes sonic signals to detect the degree of cutting edge wear in metalworking tools and automatically trigger a cutting edge change. A packaged electronic unit reads out sonic vibrations from an instrumented machine-tool workpiece cutting-tool system to determine degree of cutting edge wear during a turning cut. At a predetermined comparative sonic ratio, the electronic unit commands stoppage of the machine tool feed, retraction of the tool and auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Thus, as the crater wear progresses, the general tool geometry can vary considerably. In particular the effective rake angle increases [17]. As the rake angle increases the amount of AE generated in the cutting zone is expected to decrease, in agreement with the theoretical model (Eqn.…”
Section: Effect Of Cutting Conditions On Acoustic Emissionsupporting
confidence: 72%
See 1 more Smart Citation
“…Thus, as the crater wear progresses, the general tool geometry can vary considerably. In particular the effective rake angle increases [17]. As the rake angle increases the amount of AE generated in the cutting zone is expected to decrease, in agreement with the theoretical model (Eqn.…”
Section: Effect Of Cutting Conditions On Acoustic Emissionsupporting
confidence: 72%
“…The decrease of AE due to an increase in rake angle has actually been observed by Teti and Dornfeld [15]. Weller et al [17] also observed a reduction in sound level due to cratering. Therefore during chatter, AE generated can be reduced considerably.…”
Section: Effect Of Cutting Conditions On Acoustic Emissionmentioning
confidence: 55%
“…In the past few decades, several researchers have made significant contributions to reveal the relationship between tool wear and various features, such as forces (Krnig et al, 1972), power consumption of a spindle motor (Micheletti et al, 1976), vibration (Weller et al, 1969), and acoustic emission (Iwata and Moriwaki, 1977) for on-line tool wear monitoring. In general, there are two ways to describe the wear states of a cutting tool: one is quantitative and the other is qualitative.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1967). Weller et al (1969) used the sound emanating from the cutting operation as the indicator of tool wear. Machine operators have recognized for some time that the cutting tool emits different sounds as wear proceeds through its various stages toward tool failure.…”
Section: Introductionmentioning
confidence: 99%